Pigment and Lovastatin content on the Red Rice cultivar Bah Butong and BP 1804 IF 9 which Fermented by Monascus purpureus Jmba - ERNAWATI KASIM; NANDANG SUHARNA; NOVIK NURHIDAYAT (Society for Indonesian Biodiversity, 2006)
Research on the red rice fermented by Monascus purpureus had been done. The rice consisted of 2 cultivars such as Bah Butong and BP 1804 IF 9. The aim of the research was to know the content of the pigment and lovastatin of the fermentation result/ angkak. Angkak was powdered by using blender. To measure the content of pigment, the powder was extracted by methanol. By using spectrophotometer the content of the pigment could be measured with 390 nm wave lengths for yellow pigment and 500 nm for the red pigment. For lovastatin the powder was extracted by acetonitrile and H2SO4. By using HPLC the content of lovastatin could be measured. The results showed that the highest pigment content for yellow pigment was on the PB 1804 IF 9 cultivar, and red pigment was on the Bah Butong cultivar. The highest lovastatin content was on the BP 1804 IF 9.Key words: Monascus purpureus, red rice, pigment, lovastatin.